2013
DOI: 10.3390/antiox2040326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yeast Probiotic on Growth, Antioxidant Enzyme Activities and Malondialdehyde Concentration of Broiler Chickens

Abstract: The aim of the study was to determine the effect of yeast probiotic on body weight, and the activities of anti-oxidant enzymes: superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx), and malondialdehyde (MDA) concentration of broiler chickens. The experiment was carried out on hybrid Hubbard broiler chickens (n = 200). Two-hundred day-old chicks were randomly selected and distributed into four groups of 50 day-old chicks each: Control, C, and treatment groups comprising T1, T2 and T3 admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 31 publications
13
64
1
Order By: Relevance
“…Accordingly, Aksu et al () observed a positive effect of feeding probiotic on TBARS value of broiler meat. It is justified that nutrition plays a main role in maintaining the pro‐oxidant‐antioxidant balance (Aluwong et al, ). Similar results were reported by (Kabploy, Bunyapraphatsara, Morales, & Paraksa, ; Rajput et al, ) who addressed the addition of dietary probiotic could help in the oxidation resistance, hydroxyl radical trapping and in the antioxidant capacity increase.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Aksu et al () observed a positive effect of feeding probiotic on TBARS value of broiler meat. It is justified that nutrition plays a main role in maintaining the pro‐oxidant‐antioxidant balance (Aluwong et al, ). Similar results were reported by (Kabploy, Bunyapraphatsara, Morales, & Paraksa, ; Rajput et al, ) who addressed the addition of dietary probiotic could help in the oxidation resistance, hydroxyl radical trapping and in the antioxidant capacity increase.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were placed at room temperature for 1 h and then centrifuged at 1200 g for 10 min. The serum was stored at −80 °C to determine the metabolic profile, innate immune parameters [lysozyme, serum bactericidal activity and haemolytic complement assay (HCA)], oxidative stress and immune response to NDV antigens (Osserman and Lawlor, ; Barta and Barta, ; Amadori et al., ; Wang et al., ; Aluwong et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…A commercial kit (Diacron, Grosseto, Italy) was used to evaluate the reactive oxygen substances in the serum. Values are expressed as mmol H 2 O 2 (Aluwong et al., ). The serum antioxidant power was measured with a commercial kit (Diacron) which determines the ability of plasma to oppose the oxidative action of a hypochlorous acid (HClO) solution (Capcarova et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…A study by Aluwong et al (2013) also shows that adding a probiotic to chicken feed together with Saccharomyces cerevisiae yeast can decrease catalase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The most important enzymes with antioxidant activity are superoxide dismutase, glutathione peroxidase and catalase (Ognik and Krauze 2012). The action of these enzymes can be enhanced by feed additives such as herbs, probiotics, prebiotics or nutrient yeast, to which immunostimulatory functions are attributed (Świątkiewicz and Koreleski 2007, Cakiroglu et al 2010, Przysiecki et al 2010, Aluwong et al 2013). …”
Section: Discussionmentioning
confidence: 99%